Komparasi Metodologis Konsep Sunnah Menurut Fazlur Rahman dan Muhammad Syahrur (Perspektif Hukum Islam) - Fitria, Vita (UIN Sunan Kalijaga, 2011)
Two figures of contemporary moslem scholar, Fazlur Rahman and Muhammad Syahrur, have unique, dynamic conception and comprehension toward Sunnah and Hadits different from other scholars and moslems` comprehension in general. Both Rahman and Syahrur, emphasize more on methodological criticism on Sunnah and Hadits instead of criticism on matan and sanad. According to Rahman, the existence of hadits are historically improvable. Basically, the concept of sunnah have been existing since Islam born. It was merely guidance and protective in its nature. It embraced interpretations fit to situation and condition at the time, often considered as